Modeling systematic technology adoption: Can one calibrated representative agent represent heterogeneous agents?. (December 2019) - Chen, Huayi; Zhou, P.
Highlights: We examine whether a calibrated agent can represent heterogeneous agents. Cooperation among agents benefits the new technology's adoption. Modeling with representative agent may overestimate the policy effects. Different calibration methods will not affect the main modeling results. Abstract: This paper explores whether a well-calibrated representative-agent model can represent the heterogeneous-agent model in terms of new technology's adoption. Through two types of heterogeneous-agent model, i.e., the cooperative heterogeneous-agent model and the independent heterogeneous-agent model, this paper first illustrates that cooperation among heterogeneous agents plays an important role in the adoption of new technology. After that, this paper examines whether a well-calibrated representative-agent model reacts differently from the heterogeneous-agent model in terms of new technology's adoption under different policy interventions. Compared to the heterogeneous agents' aggregate behavior, the calibrated representative agent tends to overreact when the investment cost, risk attitude, and level of carbon tax vary. When the market size changes, however, the calibrated representative agent reacts almost the same as the heterogeneous agents' aggregate behavior.